Pengaruh Pengetahuan Keuangan Terhadap Pengelolaan Keuangan Pribadi Mahasiswa - Vanysha Bertha Ananda; Elvi Rahmi (Universitas Negeri Padang, 2023)
The purpose of this study is to determine the impact of financial knowledge on personal financial management among students of Faculty of Economics at Universitas Negeri Padang. The research was done in the form of causative research. The participants in this study are students of Faculty of Economics at Universitas Negeri Padang. Sampling is done using a simple random sampling technique. Research instruments are in the form of questionnaires for personal financial management variables, tests for financial knowledge variables. This study used descriptive analysis and induction analysis that had previously used the analysis prerequisite test. The data produced were analyzed using a partial test (t-test). The results showed that financial knowledge did not have a significant effect on the personal financial management of students of the Faculty of Economics, Padang State University. In this case, students should be able to manage their finances better and be able to apply their financial knowledge.